Abdominal decompression plays a major role in early postparacentesis haemodynamic changes in cirrhotic patients with tense ascites. Issue 3 (1st March 2001) - Cabrera, J; Falcón, L; Gorriz, E; Pardo, M D; Granados, R; Quinones, A; Maynar, M
Abstract : BACKGROUND: Some cirrhotic patients with tense ascites who undergo paracentesis develop a circulatory dysfunction syndrome, manifested by an increase in plasma renin activity. Recently, a significant inverse correlation between postparacentesis changes in plasma renin activity and systemic vascular resistance has been demonstrated in these patients, suggesting that peripheral arterial vasodilatation could be responsible for this circulatory dysfunction, but the mechanisms by which tense ascites removal induces such changes are unknown AIM: To investigate the role of a decrease in intra-abdominal pressure (IAP) in the development of early postparacentesis haemodynamic changes METHODS: Eleven cirrhotic patients with tense ascites received a large volume paracentesis. A specially designed pneumatic girdle was used to compress the abdomen to avoid a decrease in IAP during ascites removal. Haemodynamic studies were performed before paracentesis, one hour after ascites flow stopped, and 30 minutes after pneumatic girdle deflation RESULTS: When IAP was maintained at its original level, no haemodynamic changes were observed, despite large volume paracentesis. However, a significant decrease in systemic vascular resistance was seen immediately after pneumatic girdle deflation CONCLUSIONS: Early haemodynamic changes after paracentesis are avoided if IAP is maintained at its original level. The abrupt decrease in IAP could be the trigger for the development of the initial haemodynamic changes that eventually produce postparacentesis circulatory dysfunction.